PENGARUH PERTUMBUHAN EKONOMI DAN PENDUDUK TERHADAP KONSUMSI ENERGI DI INDONESIA - Yona Afrina; Rahmita budiartiningsih; Nobel Aqualdo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study’s purpose is to know how the effect of economic growth and population growth to energy consumption in Indonesia, with economic and population growth as independent variable while the dependent variable is energy consumption in Indonesia. The analysis method used in this research is descriptive and quantitative method. Data is obtained from the Ministry of Energy and Mineral Resources (MEMR) Republic of Indonesia, the Central Statistics Agency of Riau Province in the form of time series data (data of energy consumption per user sector, economic growth and population) in 2000-2013. The test statistics include F test, t test, coefficient correlation (R) and the coefficient of determination (R2). From the test results that have been done, show that economic growth variables significantly influence energy consumption of the industrial sector, commercial sector and transportation sector but the influence on the household sector and other sectors is no significant, while the population growth variables significantly influence the household sector consumption but the influence on the sector industrial, commercial sector, transportation sector and other sectors no significantly.Keywords: Energy Consumption, Economic Growth and Population Growth.